Numerical investigations of stress-deformation responses in fractured paediatric bones with prosthetic bone plates. Issue 1 (March 2020) - Kanu, Nand Jee; Patwardhan, Devendra; Gupta, Eva; Vates, Umesh Kumar; Singh, Gyanendra Kumar
Abstract: Nearly 25% of paediatric injuries happen due to fractures of femur bones, either under accidental or inflicted conditions. In the present investigation, static analyses are performed for fractured paediatric femur bones of children joined with bone plates using finite element method (FEM) approach to find stresses and deformations in the bone and plate assembly under axial compressive and torsional loadings. The investigation aims to suggest the suitable biomaterial for fracture fixation bone plates modeled using two recently-developed biomaterials such as titanium and magnesium alloys, after studying the stresses and deformations at the fracture spots of the paediatric femur bones of children aged between 1-3 years . The stress-deformation responses are further analyzed in relation to ages of the children.